Parity does not affect the reproductive response of Suizo Americano cows submitted to embryo transference in tropical areas of Guerrero - García, Ethel C.; Mendoza Medel, G.; Pineda Burgos, Blanca; Romero, Perla; Hernández Ruiz, P. E.; Vicente Pérez, R.; Valencia Franco, E.; Ponce, J. L. (Cuban Journal of Agricultural Science, 2019)
Recipient cow is the key to success in embryo transfer (ET) programs in cattle. Therefore, it is necessary to know the factors that influence on its reproductive potential. It is considered that multiparous cows have a better response to the ET program than nulliparous cows. The objective of this study was to evaluate the effect of parity on the reproductive efficiency of multiparous and nulliparous cows in a fresh ET program. Twenty-six recipient cows of Suizo Americano breed were divided into two experimental groups (n = 13/each) according to their parity (multiparous and nulliparous). Donor cows underwent a synchronization and superovulation program. Subsequently, the recipient cows were treated with fresh ET. The percentage of cows in estrus was higher on day 1 in multiparous cows than in nulliparous cows (P <0.05). On the other hand, gestation percentage, estrus time, embryo stage and pregnancy percentage per uterine horn were not significantly affected among the experimental groups (P> 0.05). In conclusion, parity did not affect the reproductive response of multiparous and nulliparous recipient cows subjected to a fresh ET program under tropical conditions. Key words: embryos, progestogens, estrus response, recipient and donor cows